2013
DOI: 10.1016/j.jconrel.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution of siRNA and cisplatin administered using CD44-targeted hyaluronic acid nanoparticles

Abstract: Multidrug resistance (MDR) is a significant problem in the clinical management of several cancers. Overcoming MDR generally involves multi-modal therapeutic approaches that integrates enhancement of delivery efficiency using targeted nano-platforms as well as strategies that can sensitize cancer cells to drug treatments. We recently demonstrated that tandem delivery of siRNAs that downregulate anti-apoptotic genes overexpressed in cisplatin resistant tumors followed by therapeutic challenge using cisplatin loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 30 publications
3
128
0
Order By: Relevance
“…Effective delivery of chemical drugs to tumor sites is particularly appealing for the enhancement of the tumor-killing effect and the reduction of systemic toxicities. 187,188 It was revealed that drug-loaded NP systems accumulate in tumors through the EPR effect, which increases drug bioavailability and prolongs the exposure to therapeutic agents. 189 Rapid uptake and retention of polymer conjugates in the lymphatic system have also been observed with low toxicity.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Effective delivery of chemical drugs to tumor sites is particularly appealing for the enhancement of the tumor-killing effect and the reduction of systemic toxicities. 187,188 It was revealed that drug-loaded NP systems accumulate in tumors through the EPR effect, which increases drug bioavailability and prolongs the exposure to therapeutic agents. 189 Rapid uptake and retention of polymer conjugates in the lymphatic system have also been observed with low toxicity.…”
Section: Drug Deliverymentioning
confidence: 99%
“…The procedure was performed according to the previously optimized protocol published by our group [47]. Briefly, 6 μl of diluted tissue sample was mixed with 18 μl of 100 nM reverse primer, and put through a cycle of denaturation by incubating at 95°C for 5 min and another cycle of annealing for 2 min at each temperature of 80, 70, 60 and 45°C.…”
Section: Whole Body and Ex Vivo Nir Imagingmentioning
confidence: 99%
“…Overexpression of bcl-2 is known to delay the onset of apoptosis induced by several chemotherapeutic drugs. Evidence reported indicates that downregulation of antiapoptotic genes such as survivin and bcl-2 can sensitize cancer cells to anticancer drugs (45,46). We have previously observed the effect of combining siRNA and cisplatin in CD44-targeting hyaluronic acid (HA)-based self-assembling nanosystems reversed drug resistance and delayed the tumor growth significantly (growth inhibition increased from 30 to 60%) in cisplatin-resistant tumors without indication of non-specific toxicity (Fig.…”
Section: Overcoming Mdr By Modulating Apoptotic Genes and Proteinsmentioning
confidence: 94%